Pleiotropic Role of Tenascin-C in Central Nervous System Diseases: From Basic to Clinical Applications - Hanmin, Chen; Xiangyue, Zhou; Lenahan, Cameron; Ling, Wang; Yibo, Ou; Yue, He (Frontiers in Neurology, 2020)
Abstract: The extracellular matrix is composed of a variety of macromolecular substances secreted by cells, which form a complex network that supports and connects tissue structures, regulates the occurrence of tissues and maintains the physiological activities of cells. Tenascin-C, a secreted extracellular matrix glycoprotein, is abundantly expressed under the pathological stimuli. It plays an important regulatory role in brain tumours, vascular diseases, and neurodegenerative diseases by mediating inflammatory responses, inducing brain damage and promoting cell proliferation, migration and angiogenesis through multiple signal pathways. Therefore, tenascin-C may become a potential therapeutic target for intracranial diseases. Here, we search and discuss the latest literature about tenascin-C and comprehensively explain the role and clinical significance of tenascin-C in intracranial diseases.